Implementation of Field Experience Practices 1 Pre-Service PPG Batch 2 Year 2023 at SMA Negeri 8 Pontianak - Imran, Imran; Partiwi, Sri Uji; Juliantara, Juliantara; Sabirin, Sabirin; Fadhilah, Muhammad Arif (Universitas Tanjungpura, 2024)
This article discusses the professional education program for teachers as educators and teaching staff in order to improve the quality of education and the efforts made to increase this professionalism. This article aims to present the results of the evaluation in the implementation of practical field experience (PPL) 1 for prospective teachers in the 2nd batch of Pre-service PPG students in 2023 at SMA Negeri 8 Pontianak which focuses on the experiences, challenges and results of these activities. This research uses a descriptive method qualitative with observation, interviews and documentation instruments. The findings from this research show that the implementation of PPL 1 for Pre-Service PPG students, batch 2 in 2023 at SMA Negeri 8 Pontianak went well and resulted in a variety of experiences for prospective teachers. PPL 1 activities at SMA Negeri 8 Pontianak will be held from January 15 2024 to March 5 2024. These activities include orientation, observation, teaching assistance, guided learning practices. The results found from this activity were the challenges faced including coordination between educational institutions and partner schools, as well as adaptation obstacles experienced by PPG Pre-service students to the new environment. However, the evaluation results show that the majority of prospective teachers felt a positive impact from this experience and increased their understanding of the professional world as a teacher. In conclusion, the implementation of PPL 1 for PPG Pre-service students in batch 2 in 2023 at SMA Negeri 8 Pontianak made a positive contribution in preparation prospective teachers to face their future duties so that continuous efforts are needed to improve the effectiveness of PPL1 implementation to ensure that prospective teachers are truly prepared to face the demands of their profession.